Development of E-Module based on Guided Inquiry Integrated to Virtual Laboratory Acid-Base Titration Materials for Class XI - Rahlia Ayu Putri; Andromeda Andromeda (Entalpi Pendidikan Kimia, 2022)
This study aims to determine the categories of validity and practicality of the e-modules that have been produced. The type of research is classified as a 4-D model, which has four stages, namely the define, design, develop, and disseminate stages. The instruments used are a validation sheet and a practical sheet in the form of a questionnaire sheet. The resulting product was tested for validity by 5 validators, consisting of 3 lecturers majoring in chemistry at FMIPA UNP and 2 teachers from SMAN 1 Rao, Pasaman Regency. Practicality tests were carried out by 2 chemistry teachers along with 15 students in class XI MIPA SMAN 1 Rao, Pasaman District. Based on the validation results, the value of kappa moment (k) is 0.86. The practicality of teachers and students is then obtained by the average value of kappa moment (k) of 0.90 and 0.88. The value obtained indicates that the resulting e-module is categorized as very valid and practical.